Biotransformation of chlorothalonil by strain Stenotrophomonas acidaminiphila BJ1 isolated from farmland soil - Qingming Zhang; Hongyu Liu; Muhammad Saleem; Caixia Wang (Royal Society Open Science, 2019)
Chlorothalonil is a widely used fungicide, but the contamination of soil and water environments by this chemical causes potential threats to biodiversity. Given the metabolic potential of soil microorganisms, there is a need for developing microbiological approaches to degrade persistent compounds, such as chlorothalonil, in contaminated sites. Here in this study, we isolated a bacterial strain (namely, BJ1) capable of degrading chlorothalonil from a chlorothalonil-contaminated farmland soil in the Shandong Province, China. Using 16S rDNA gene sequencing, morphological and biological characteristics, we identified the strain BJ1 as Stenotrophomonas acidaminiphila. The strain BJ1 uses chlorothalonil as a sole carbon source. At initial concentrations of 50, 100, 200 and 300 mg l−1, it degraded 91.5%, 89.4%, 86.5% and 83.5% of chlorothalonil after 96 h of inoculation under optimum conditions (30°C and pH 7.0). Two metabolites, methyl-2,5,6-trichloro-3-cyano-4-methoxy-benzoate and methyl-3-cyano-2,4,5,6-tetrachlorobenzoate, were detected and identified based on HPLC–MS analysis, which suggests that the strain BJ1 metabolized chlorothalonil through the hydroxylation of chloro-group and hydration of cyano-group. The results of this study highlight the great potential for this bacterium to be used in chlorothalonil pollution remediation.